Watta Satta : Bride Exchange And Women's Welfare In Rural Pakistan - Jacoby, Hanan (The World Bank, 2007)
In a setting where husbands wield considerable coercive power, forms of marriage should adapt to protect the interests of women and their families. The authors study the pervasive marriage custom of watta satta in rural Pakistan, a bride exchange between families coupled with a mutual threat of retaliation. They show that watta satta may be a mechanism to coordinate the actions of two sets of in-laws, each of whom wish to restrain their sons-in-law but who only have the ability to restrain their sons. The authors' empirical results support this view. The likelihood of marital inefficiency, as measured by estrangement, domestic abuse, and wife's mental health, is significantly lower in watta satta arrangements as compared with conventional marriages, but only after properly accounting for selection